Actinomyces turicensis Bacteremia Secondary to a Decubitus Ulcer: A Case Report and Review of the Literature. Issue 5 (September 2018) - Snead, Jessica A.; Ruggiero, Nicole; Sangha, Ruby; Joseph, Leian; Mukherji, Rajat
Abstract : Abstract: We present a rare case of Actinomyces turicensis bacteremia secondary to a polymicrobial sacral decubitus ulcer infection in an elderly male patient. A PubMed search revealed only 9 previously reported cases of bacteremia due to A. turicensis, mostly in female patients. Because Actinomyces species are commensal organisms of the gastrointestinal tract, sacral decubitus ulcers may have an increased propensity of becoming infected and consequently cause a bacteremia. Our patient was successfully treated with debridement and intravenous antibiotic therapy; however, the optimal antibiotic treatment and length of therapy remain unclear because only a few case reports exist in the literature. Abstract : The authors present a rare case of Actinomyces turicensis bacteremia secondary to a polymicrobial sacral decubitus ulcer infection in an elderly male patient. The patient was successfully treated with debridement and antibiotic therapy. A PubMed search revealed only nine previously reported cases of A. turicensis bacteremia, mostly in female patients.